Dessulfurização de biogás utilizando íon ferro III adsorvido em resina de troca iônica - Thrun, Matheus Damasio (2023)
Fossil fuels face a severe crisis due to continued population growth as well as dwindling natural reserves. In this context, the production of energy from biogas generated by anaerobic digestion of different types of waste presents itself as an excellent alternative. However, small fractions of hydrogen sulfide (H2S) are found in the composition of biogas, which cause damage to generators, corrosion in installations and the emission of sulfur oxides into the atmosphere. To avoid this damage, it is recommended to purify the biogas. From this, studies were carried out in a bench-scale purification system to reduce the concentration of H2S present in biogas, where its reaction with iron III ions (Fe3+) produces iron II ions (Fe2+) and elemental sulfur (S0). Subsequently, Fe2+ is oxidized into Fe3+ by oxidation with oxygen present in atmospheric air. To carry out the adsorption of Fe3+, the ion exchange resin (IER) Dowex® MarathonTM C hydrogen form was adopted. The preparation of Fe3+/RTI occurred by placing IER in contact with a solution containing Iron III Chloride hexahydrate. For the desulfurization tests, a sulfide (S2-) solution was prepared and kept inside a bottle with 1.5 g of the Fe3+/IER resin. After verifying that the Fe3+/IER system has lost efficiency, it is necessary to regenerate with oxygen and repeat the steps five times, in order to verify the repeatability and maintenance of system efficiency. With this it was possible to verify the concentration of S2- in which a removal greater than 72% was observed in all tests carried out, the concentration of Fe3+ in the output solution was monitored, which resulted in an adsorption of 89.5% indicating that Fe3+ remained bound in IER and it was also verified that IER has the ability to remove S2- ions and possibly convert S2- into S0 as verified in X-ray spectroscopy analyzes coupled to an electron microscope scanning (EDS-SEM). Therefore, the Fe3+/IER system is able to treat aqueous solutions containing absorbed H2S.